The development of executive function - Girdzijauskienė, Sigita; Rakickienė, Lauryna (Psichologija, 2012)
Executive function is a group of the higher-order cognitive abilities that coordinate and monitor other abilities and behavior. As complex cognitive functioning is primarily attributed to adults, executive function in children has rarely been studied. However, research of executive function from the perspective of developmental psychology and psychopathology has become more frequent in recent decade. Several findings have attributed to this change, the discovery of an intriguing connection between children’s executive function and theory of mind among them. Several reviews have been published in the field, providing the detailed developmental map of most often studied components of executive function (Garon et al., 2008; Best et al., 2009). However, they touch less on the broader context of executive function development. The aim of this review paper is to discuss the main findings, new trends and unanswered questions associated with developmental research in executive function, hoping this will stimulate Lithuanian psychologists become more involved in the field.We start the first part of the paper by discussing the difficulties in developmental research of executive function associated with the theoretical ambiguity of the construct and methodological problems. Most authors have focused to three main executive functions in recent years: mental set shifting, working memory updating and response inhibition. However, none of the neuropsychological tests measure isolated component of executive function, which makes the interpretation of the findings complicated. Studying executive function in young children at least partly addresses this problem, as the neuropsychological tasks are less complex, so more “pure” in this group. We briefly describe the developmental trends of main executive functions, concluding that the development of these abilities starts as early as the first year of life, undergoes the biggest changes in preschool years and continues till late childhood and even adulthood. We finally outline the importance of studying psychosocial context of the development of executive function. There is evidence that early social interaction may affect the development of executive function (Bibok et al., 2009; Bernier et al., 2010), but much remains to be done to better understand the mechanisms of the development of these functions. The second part of the paper is devoted to the connection between the development of executive function and theory of mind. There are four main proofs of this connection: 1) positive correlation between the executive function and theory of mind test results; 2) matching developmental paths of these two psychic functions; 3) matching brain regions; 4) disorders of both psychic functions in case of psychopathology (autism disorder in particular). Although the connection between executive function and theory of mind development is well documented, little is known about the nature and direction of this connection. The most prominent hypothesis is that executive function development stimulates the emergence of executive function (Carlson et al., 2004; Hughes and Ensor, 2007), but alternative explanations exist. We suggest that the explanations taking into account the social context of the development of both psychic functions should be considered.
Keywords: executive function; theory of mind; autism; early social relationship